Mid-term Follow-Up after Closed Reduction in Developmental Dysplastic Hips - Walter, Sebastian G.; Ossendorff, Robert; Bornemann, Rahel; Zarghooni, Kourosh; Peterlein, Christian Dominik; Placzek, Richard (Zeitschrift für Orthopädie und Unfallchirurgie, 2022)
Purpose Closed reduction and subsequent spica casting is the gold standard for treatment of unstable or dislocated developmental dysplastic hips (DDHs). There are few data on mid-term results after treatment of DDH, especially on closed reduction.Methods Thirty-one consecutive patients with unstable or dislocated hips (n = 36) that were treated by fluoroscopic, contrast agent-supported closed reduction and spica casting were included and evaluated clinically and radiologically 2 and 5 years after treatment.Results After 2 and 5 years, there were no significant differences between healthy and successfully treated hips that were detectable with respect to acetabular coverage (AC) angle, center-edge angle, and clinical stability of the hip. There was a significant difference at the 2-year follow-up between healthy hips and hips that needed to undergo secondary open reduction surgery (n = 4) with respect to the AC angle (p < 0.001).Conclusion Closed reduction in DDHs results in acceptable clinical and radiological results in the mid-term follow-up. It remains unclear why some patients with subsequent sonographically matured hips show secondary deterioration and recurrence of dysplasia.
Keywords: DDH; closed reduction; dysplasia; Graf; hip dislocation